2020
DOI: 10.3389/fpsyg.2020.01305
|View full text |Cite
|
Sign up to set email alerts
|

Social Competence and Peer Social Acceptance: Evaluating Effects of an Educational Intervention in Adolescents

Abstract: This study aims to evaluate the impact of an educational intervention on social competence and social acceptance among adolescents. The participants were 106 adolescents aged 12-15 years (M = 13.41 years; SD = 0.81 years). Participants were randomly assigned to the control group (n = 44) and an experimental group (n = 69). In the experimental group, an intervention based on the Sport Education Model (SEM) was applied. While in the control group, an intervention based on the Traditional Model of Direct Instruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 70 publications
2
23
0
2
Order By: Relevance
“…Among the studies examined, the following variables were identified relative to the development of personal and social skills: autonomy (e.g., Cuevas et al, 2015); motivation (e.g., Cuevas et al, 2016), competence, relatedness (e.g., Viciana et al, 2020), enjoyment/satisfaction (e.g., Browne et al, 2004), sportsmanship (e.g., Méndez-Gimenez et al, 2015), physical self-concept (Fernandez-Rio et al, 2013), cooperation (e.g., Viciana et al, 2020), friendship (e.g., Rocamora et al, 2019), group cohesion (e.g., Kao, 2019), self -efficacy, peer social acceptance (Luna et al, 2020a), emotional intelligence, social anxiety, subjective well-being (Luna et al, 2020b), and affect (Perlman, 2010).…”
Section: Findings About the Development Of Students' Personal And Socmentioning
confidence: 99%
“…Among the studies examined, the following variables were identified relative to the development of personal and social skills: autonomy (e.g., Cuevas et al, 2015); motivation (e.g., Cuevas et al, 2016), competence, relatedness (e.g., Viciana et al, 2020), enjoyment/satisfaction (e.g., Browne et al, 2004), sportsmanship (e.g., Méndez-Gimenez et al, 2015), physical self-concept (Fernandez-Rio et al, 2013), cooperation (e.g., Viciana et al, 2020), friendship (e.g., Rocamora et al, 2019), group cohesion (e.g., Kao, 2019), self -efficacy, peer social acceptance (Luna et al, 2020a), emotional intelligence, social anxiety, subjective well-being (Luna et al, 2020b), and affect (Perlman, 2010).…”
Section: Findings About the Development Of Students' Personal And Socmentioning
confidence: 99%
“…Por tanto, como se menciona anteriormente, la afiliación a un equipo repercute en los comportamientos sociales de los alumnos y puede hacerlo con diferentes matices. Luna et al (2020) enfatizan la idea de que los resultados obtenidos con adolescentes a través de la ED pueden estar más cerca de obtener la eficacia en la interacción social que a la aceptación dentro de un grupo. En cambio, en el presente estudio los resultados muestran como las interacciones surgidas dentro de un grupo concreto permiten la mejora de las relaciones a un nivel más general e incluso se pueden extrapolar fuera del aula.…”
Section: Discussionunclassified
“…Likewise, these physical and sports activities within physical education are beneficial for students from the integral perspective of the child [22,23]. There is some empirical evidence that physical education could be a significant psychoeducational intervention for developing effective forms of physical/sporting experiences, which will improve students' socio-emotional competencies [24,25]. Physical education promotes a significantly flexible and cooperative environment favoring intrapersonal and interpersonal interactions among students [26].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the SEM has generated significant interest in scientific literature, with the publication of different reviews [38][39][40][41][42] and meta-analyses [43]. It is an effective teaching model that shows significant improvements in the educational context, in both students' well-being [44] and socio-emotional development [25,37,40,45]. Similarly, it is an empirically validated model where recent findings, in line with the variables under study, show improvements in social indicators [25,37,[45][46][47], as well as affective or emotional indicators [24,44,48].…”
Section: Introductionmentioning
confidence: 99%